Early Marriage in Islam: A Comparative Study of Shāfi‘ī Fiqh and Indonesian Positive Law - Iqbal Sabirin, Muhammad; Anggarini, Ida Fitri (Al-Mizan, 2025)
Early marriage has sparked controversy from both the perspective of Islamic law and Indonesia’s positive law. In Shāfi‘ī jurisprudence, there is no stipulation regarding a minimum age for marriage; thus, marriage conducted below the age of puberty is still considered valid. In contrast, Indonesia's positive law, through Law Number 16 of 2019, sets the minimum legal age for marriage at 19 years for both men and women, with certain exceptions permitted through a court-issued dispensation. This study employs a qualitative-descriptive approach through library research and a comparative method to analyze the similarities and differences between the two legal frameworks. The findings reveal that although there are fundamental differences concerning the legal age of marriage, both systems ultimately aim to achieve public welfare (maslahah) and prevent harm (mafsadah). The state assumes a protective role by establishing a minimum marriage age to safeguard children from the negative consequences of early marriage, in accordance with the Islamic legal maxim dar’u al-mafāsid muqaddamun ‘alā jalbi al-mashālih (preventing harm takes precedence over acquiring benefits). Therefore, state regulations may be viewed as an implementation of Islamic legal values in a contemporary social context.